If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 1 = 4x + 5 Combine like terms: 6 + 1 = 7 7 = 4x + 5 Reorder the terms: 7 = 5 + 4x Solving 7 = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + -4x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + -4x = 5 + 0 7 + -4x = 5 Add '-7' to each side of the equation. 7 + -7 + -4x = 5 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 5 + -7 -4x = 5 + -7 Combine like terms: 5 + -7 = -2 -4x = -2 Divide each side by '-4'. x = 0.5 Simplifying x = 0.5
| 3.3x+7.3=9.4+2.7x | | lx-3l+lx-11l=8 | | 8x+5=15+3x | | 7x^2+12y^2= | | 7x+9=39+2x | | 7x+9=39+2z | | -3.6x-6.9-8x=-5.5 | | (9y+18)+(5x+x)=90 | | 9(4w-8)=12(3w+5) | | 2(3x-4)-12=(5x-3) | | 9y+18+5x+x=90 | | 9x+5+3x+1=90 | | Y=a+bx+cx^2+dx^3 | | 8x+6y=450 | | 2x+14=20-4x | | -30=5y-5 | | 8x+16=106-2x | | 21-7x=39-10x | | (4w+3)*2w=9w | | -17m-11=-9m-59 | | 7x+9=29-3x | | 3x+8=38-2x | | x-2+3=12 | | 3(2x+1)-4(x-2)=25 | | f(x)=-3x^2+15 | | 5*5+7-3= | | 110=w(w+15) | | W^2+15w=110 | | 4xy-4xz= | | t^2-3t=-2 | | 2=16-2p | | 12y^2+y-20=0 |